Chromatin Regulation in the Response of Ethylene: Nuclear Events in Ethylene Signaling. Issue 8 (4th July 2019) - Wang, Likai; Zhang, Fan; Qiao, Hong
Abstract: Plant hormones, produced in response to environmental stimuli, regulate almost all aspects of plant growth and development. Ethylene is a gaseous plant hormone that plays pleotropic roles in plant growth, plant development, fruit ripening, stress responses, and pathogen defenses. After decades of research, the key components of ethylene signaling have been identified and characterized. Although the molecular mechanisms of the sensing of ethylene signal and the transduction of ethylene signaling have been studied extensively, how chromatin influences ethylene signaling and ethylene response is a new area of research. This review describes the current understanding of how chromatin modifications, specifically histone acetylation, regulate ethylene signaling and the ethylene response. Abstract : This review summarizes the recent progress of chromatin regulation, specifically histone acetylation in the ethylene response. The review also proposes future research directions of chromatin regulation in the ethylene response and ethylene signaling.